Beyond Keynesianism Global Infrastructure Investments in Times of Crisis - Lin, Justin Yifu (The World Bank, 2012)
As the world recovers only slowly from the 2008 financial crisis and Europe is facing a looming debt crisis, concerns have increased that the "new normal"-a period of high unemployment, low returns on investment, high risks, and low growth-may become protracted in advanced economies. If growth remains weak, unemployment rates and debt levels will be slow to recede. Consequently, the global recovery may continue to be fragile for years to come. What the world needs now is a growth-lifting strategy. This strategy could take the form of a global infrastructure initiative. Since debt levels are high, governments in the United States and Europe could increase demand and support growth through investments in bottleneck-releasing infrastructure projects that are self-financing. An infrastructure initiative should, however, go beyond the borders of advanced countries and include developing countries. Economic and social returns to infrastructure investments tend to be high in developing countries, which have become increasingly important drivers of global growth. At the same time, infrastructure investments require capital goods, most of which are produced in high-income countries. Scaling up infrastructure investment in developing countries could therefore help generate a virtuous cycle in support of a global recovery